Plasma riboflavin fluorescence as a diagnostic marker of mesenteric ischemia-reperfusion injury in rats. Issue 223 (March 2023) - Wu, Xueqin; Guo, Lun-Zhang; Liu, Yi-Hung; Liu, Yu-Cheng; Yang, Po-Lun; Leung, Yun-Shiuan; Tai, Hwan-Ching; Wang, Tzung-Dau; Lin, Jesse Chih-Wei; Lai, Chao-Lun; Chuang, Yueh-Hsun; Lin, Chih-Hsueh; et al.
Abstract: Due to the delayed and vague symptoms, it is difficult to early diagnose mesenteric ischemia injuries in the dynamics of acute illness, leading to a 60–80 % mortality rate. Here, we found plasma fluorescence spectra can rapidly assess the severity of mesenteric ischemia injury in animal models. Ischemia-reperfusion damage of the intestine leads to multiple times increase in NADH, flavins, and porphyrin auto-fluorescence of blood. The fluorescence intensity ratio between blue-fluorophores and flavins can reflect the occurrence of shock. Using liquid chromatography and mass spectroscopy, we confirm that riboflavin is primarily responsible for the increased flavin fluorescence. Since humans absorb riboflavin from the intestine, its increase in plasma may indicate intestinal mucosa injury. Our work suggests a self-calibrated and reagent-free approach to identifying the emergence of fatal mesenteric ischemia in emergency departments or intensive care units.